Financial Literacy on Saving Behavior in MSMEs with Social Influence as an Intervening Variable - Aureliea Tarisha; Kevin Herdiyanto Ardi; Irfan Nafis Fatkhurrahman; Farah Margaretha Leon (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
Saving behavior is currently a problem for some people, especially for MSMEs. They sometimes have a high net income, but often they fail to get some of the money to save or even invest. This study aims to find out if financial literacy significantly influences saving behaviors moderated by social influences. They are saving behavior as a dependent variable, financial literacy as an independent variable, social influence as an intervening variable, age, gender, marital status, and education level as the control variable. The number of samples in the study was obtained by 200 respondents referring to small and medium-sized micro-enterprises in the processing industry sector located in DKI Jakarta. The data analysis method uses structural equation modeling (SEM) analysis tools. The findings of this study showed that social influence, age, gender, marital status, and level of education had no significant effect on saving behavior. There is a novelty in the study that is with multiple designs on social influence variables. With this research, it is expected that MSME managers can improve their financial literacy by attending workshops and financial training in pandemic situation.